IMPLEMENTATION OF PAI TEACHER RESPONSIBILITIES IN ONLINE LEARNING DURING THE COVID 19 PANDEMIC - Azimah, Azimah; Salami, Hafidz (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
The teacher's responsibilities in assessing learning include: carrying out assessments using assessment instruments that have been developed when planning learning; carry out modifications and scoring; as well as providing input and follow-up on process improvements and providing remedial learning. The skills needed to carry out learning assessment tasks are to understand the learning assessment methodology, including assessment techniques and tools, good assessment criteria, forms and types of tests, scoring, statistics related to assessment, as well as remedial implementation programs. Therefore, a teacher needs to motivate students to carry out activities to meet their needs. Because motivation can make someone try to improve the work results they want to achieve. This effort will continue until you get what you want. This motivation arises because of a need. The needs that encourage motivation are psychological needs to fulfill physical satisfaction such as eating, drinking, oxygen and so on as well as social psychological needs to fulfill social satisfaction such as; appreciation, praise, security and so on. Apart from that, the emergence of motivation is also influenced by the environment in which the individual is located.